A SEMANTIC STUDY OF THE VARIETY OF VERBS USED BY SPORTSWRITERS IN DESCRIBING WINNING AND LOSJNG IN THE JAKARTA POST'S SPORT SECTION - KHUZAIYIN ANSHORI (2000)
Based on the observation when reading newspapers. especially the sports section. the writer found that the sportswriters (writers of the sport section) use a large variety of verbs to describe winning and losing in giving account of the results of sport events. In particular, he found the phenomenon in football news. He was, then, interested to look into the phenomenon in depths and develop it into a thesis. In this thesis. the writer tries to determine what (kinds of) verbs the sportswriters use in their description of winning and losing and to find out the reason and particularly the contexts that underlie the use of verbs. On his analysis, he finds that there are forty verbs commonly used to describe winning and twenty verbs to allude to losing. The writer describes the use of the verbs describing winning and losing in relation to its contextual and semantic values. By the former value, the discussion is in the range of knowing the contexts that underlie the use of the verbs in sentences reporting winning and losing events - as the scores of the game and whether one team is favored or not over the other. By the second, the discussion is in the range of knowing the semantic values of the verQs. It is assumed that the verbs are used to describe winning and losing because there arc similarities of meaning between the verbs.